Managing a broadcast newsroom during a crisis: the case of three campus radio stations during the Covid-19 pandemic in South Africa in 2020 - Rowland, Viviene Jennifer (Stellenbosch : Stellenbosch University, 2023)
Thesis (MEd)--Stellenbosch University, 2023.